Efektivitas Bakteri Bacillus subtilis terhadap Kelulushidupan Ikan Nila (Oreochromis niloticus) yang Diinfeksi Bakteri Pseudomonas fluorescens - Budianto; Ihza Farras Faadhilah; Aprilia Ekawati; Silvia Anggaita; Qurrota A’yunin; Sri Andayani (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
A bacterial disease that infects freshwater fish, especially tilapia (Oreochromis niloticus), is a septicemia disease caused by Pseudomonas fluorescens infection. The purpose of this study was to determine the effectiveness of Bacillus subtilis on the survival of tilapia infected with P. fluorescens in vivo. The doses of B. subtilis used were different for each treatment, namely A (104 CFU/ml), B (106 CFU/ml), and C (108 CFU/ml). Fish were kept for 7 days to calculate their survival rate. Dosage of B. subtilis bacteria had a significant effect (α > 0,05) on the survival of tilapia infected with P. fluorescens bacteria. The best dose of B. subtilis in treatment A (104 CFU/ml) could increase the survival rate of tilapia infected with P. fluorescens with a survival rate of 93.33 ± 11.55%. The average ranges of water quality during the maintenance period are 25°-30°C, pH 7.2-9, and dissolved oxygen 5.50-7.00 ppm.